A DEVELOPMENT MODEL OF FUZZY GOAL PROGRAMMING FOR REGIONAL RIVER WATER QUALITY MANAGEMENT - Udisubakti Ciptomulyono (Purifikasi, 2007)
This paper proposes a development of Fuzzy Goal Programming model with imprecise information goal for optimizing the regional water quality management. Imprecision is associated with fuzziness which is non-statistical in nature and refers to the absence of sharp boundary in the information. Imprecise standards in environmental management objective could be represented by fuzziness functions. The objectives of management to be achieved in this model are categorized as: (i) Environmental objectives i.e. to maintain an ambient water quality in two parameters and standards, BOD(Biochemical Oxygen Demand) and DO (Dissolved Oxygen) closed to desired stream standard goal and to achieve an improvement sanitation program target;(ii) Economic objective i.e. to minimize the total cost of removing residual by an alternatives waste of treatment systems. The model of "Streeter Phelps" is adopted to represent the ecological relationship between organic pollutant loading and fluctuated water quality. Then fuzzy goal programming is developed as one of Multi Criteria Decision Making (MCDM) approach to "optimize" the objectives of decisions, in order to calculate how many pollutant should be removed at each system. The solution of the model provides a way of trade off analysis between attainment of objectives and useful imprecise information to the decision maker of environmental planning